1972
DOI: 10.1136/gut.13.8.627
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of spontaneous duodeno-colic fistula

Abstract: SUMMARY Three cases of duodeno-colic fistula are presented, where a communication was demonstrated between the anterior aspect of the third part of the duodenum and the transverse colon at the point of mesocolic attachment. At operation the fistulae were found to be some 6 to 9 cm in length, and histological examination showed a well marked muscular layer with an intact epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Spontaneous colo-duodenal fistulae have also been reported. [10] Malignant causes other than colonic carcinoma, include carcinoma of the gall bladder, [11] duodenum [12] and even of the esophagus. [13] In most instances of duodeno-colic fistula, the second part of the duodenum is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous colo-duodenal fistulae have also been reported. [10] Malignant causes other than colonic carcinoma, include carcinoma of the gall bladder, [11] duodenum [12] and even of the esophagus. [13] In most instances of duodeno-colic fistula, the second part of the duodenum is involved.…”
Section: Discussionmentioning
confidence: 99%
“…All three patients had excision of the tract and settled post-operatively. These fistulae were always from the mid transverse to the duodenum and not related to inflammatory bowel disease – the pathology was non-specific and the authors postulated a congenital cause [28]. …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that individuals in loose cultures are more likely to succeed in creative tasks than individuals in tight cultures (Chua et al., 2015), and tight cultures are less receptive to novel ideas deviating from accepted ways of life or thinking (Shane, 1992; Jones and Davis, 2000; Niu and Sternberg, 2001). Furthermore, individualistic cultures value originality, an essential component of creativity (Torrance, 1972), compared with collectivist cultures (Bechtoldt et al., 2010).…”
Section: Fostering Creative Thinking: Cultural Considerationsmentioning
confidence: 99%
“…Decades ago, Torrance (1972) analyzed and summarized 133 studies that were designed to examine whether children can be taught to think more creatively. His review indicated that it is possible to teach children to think more creatively.…”
Section: Fostering Creative Thinking: Developmental and Pedagogical Cmentioning
confidence: 99%